HUBUNGAN WAKTU LAMA TUNGGU DENGAN KECEMASAN PADA PASIEN PRE OPERASI SECTIO CAESAREA DENGAN SPINAL ANESTESI DI RSUD dr. SOEDIRMAN KEBUMEN - Vilda Ardya Putri; Amin Susanto; Siti Haniyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background:Most patients before sectio caesarea surgery using spinal anesthesia have different waiting times, which affects preoperative anxiety. Overreaction due to this anxiety is feared to affect the success of the surgery. The long waiting time of preoperative sectio caesarea patients (?30 minutes) has moderate anxiety. While inappropriate pre anesthesia waiting time (>30 minutes) has severe anxiety. Therefore, the longer the waiting time experienced by patients can affect the level ofanxiety in patients. Purpose:This study aims to determine the relationship between waiting time and anxiety of preoperative sectio caesarea with spinal anesthesia Methods:This study used quantitative correlation analytics with a cross sectional approach.Data collection was carried out before the respondent entered the operating room by giving the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. The sample in this study was 66 respondents who were taken using purposive sampling technique. Data analysis used isu nivariate and bivariate analysisusing the spearman rank test. Result:The results of the correlation statistical test using Spearman rank showed that the coefficient method was 0.5 and p value 0.000. From this study it is known that out of 51 people in the category of waiting time ?30 minutes, there are 26 people (39.4%) with moderate anxiety, in the >30 minute category, there are 8 people (12.1%) with severe anxiety. Conclusion:There is a relationship between waiting time and anxiety in preoperative sectio caesarea patients with spinal anesthesia at RSUD Dr.Soedirman Kebumen.